Jack Wilson papers - Wilson, Jack, approximately 1841-
Diaries, roster book, Special Orders No. 106, and a military discharge certificate relating to Wilson's service with Company F, 30th Wisconsin Infantry Regiment during the Civil War and Indian campaigns in the Great Plains and Dakota Territory. Wilson describes Indian customs and culture, buffalo hunting expeditions of Indians and soldiers, treatment of Confederate prisoners, and the assignments and conduct of African American soldiers at Rock Island prison. In his 1863-1864 diary, Wilson includes Lakota words with English translation. A post-war diary contains financial accounts from 1855-1856 and 1866.
Union Army soldier and farmer. Name possibly Jackson Wilson.
Collection material in English, with Lakota (Siouan).
Keywords: United States. -- Army. -- Wisconsin Infantry Regiment, 30th (1862-1865); American bison hunting; Indians of North America -- History -- Civil War, 1861-1865.; Indians of North America -- Hunting; Indians of North America -- Social life and customs; Indians of North America -- Wars -- 1862-1865.; Indians of North America -- Wars -- Dakota Territory; Indians of North America -- Wars -- Great Plains; Prisoners of war -- United States; Soldiers -- Confederate States of America; Dakota Territory -- History; Great Plains -- History; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Farmers; Soldiers